Evaluation of pre- and postnatally diagnosed gastrointestinal tract obstructions. (2nd October 2019) - Orgul, Gokcen; Soyer, Tutku; Yurdakok, Murat; Beksac, Mehmet Sinan
Abstract: Purpose: Signs of congenital obstruction of the gastrointestinal tract (GIT) organs may present on prenatal ultrasonography. Prenatal detection is influenced by several factors, including obstruction site, lesion degree (partial or complete), the occurrence of associated malformations, and gestational week at screening. Here, we aimed to evaluate the success of prenatal diagnosis of GIT obstructions in a tertiary center in Turkey. Materials and methods: The study included 34 prenatally and 22 postnatally diagnosed babies with different GIT malformations. GIT obstructions were divided into five groups according to the level of obstruction (A. esophagus, B. stomach and proximal duodenum, C. small intestine, D. large intestine, E. multiple obstructions). Results: The prenatal detection rate among all cases was 60.7%. The associated structural malformation and aneuploidy rates were 21.4 and 5.4%, respectively. Twelve neonates died within the first day after birth due to various reasons. The remaining 43 babies underwent surgery at different times according to their clinical conditions. The mean time between birth and surgery was 4.5 days (range, 1–56 days). There were 12 postoperative deaths due to various complications, and one case died at 2 years of age. Overall, 31 of the 56 (55.4%) babies were alive during the follow-up period. The successful prenatal diagnosis rates were 57.2, 85.8, 75, 25, and 80% in groups A, B, C, D, and E, respectively. The median birth weight increased significantly in groups A through D ( p = .04). However, there were no intergroup differences in the Apgar scores, associated abnormality rates, time to surgery, and number of babies operated. Conclusions: These findings demonstrate the importance of prenatal ultrasonography and success of prenatal detection especially for upper GIT abnormalities. Although there are some prenatal signs of GIT obstructions, such as double bubble, polyhydramnios, enlarged bowel, and failure to visualize the stomach, early prenatal diagnosis is difficult and can be delayed, resulting in the detection of GIT obstruction after birth. When suspecting GIT obstruction, clinicians should evaluate the fetal anatomy carefully and be aware of associated chromosomal abnormalities.